Video consultations in primary and specialist care during the covid-19 pandemic and beyond - Car, Josip (2022)
Even before the covid-19 pandemic, virtual consultations (also called telemedicine consultations) were on the rise, with many healthcare systems advocating a digital-first approach.1 -7 At the start of the pandemic, many GPs and specialists turned to video consultations to reduce patient flow through healthcare facilities and limit infectious exposures.8 -16 Video and telephone consultations also enable clinicians who are well but have to self-isolate, or who fall into high risk groups and require shielding, to continue providing medical care.17 -19 The scope for video consultations for long term conditions is wide and includes management of diabetes, hypertension, asthma, stroke, psychiatric illnesses, cancers, and chronic pain.20 -22 Video consultations can also be used for triage and management of a wide range of acute conditions, including, for example, emergency eye care triage.23 -25 This practice pointer summarises the evidence on the use of video consultations in healthcare and offers practical recommendations for video consulting in primary care and outpatient settings.